Some statistics and researches on the Poor Removal question, with special reference to the removal of persons of Irish birth from Scotland - Hancock, W. Neilson (Statistical and Social Inquiry Society of Ireland, 1879)
In the course of some researches upon the ages of persons of Irish birth in England and Scotland, I arrived at some figures which place in a strong point of view the very large proportion of persons liable to be affected by the laws as to poor removal from Scotland and England to Ireland.
Read before the Society, August 1878
Keywords: Poverty; Poor removal; Irish diaspora; Welfare; 314.15